KONSEP AFÄL AL-IBÄD DALAM PEMIKIRAN TEOLOGI TOKOH-TOKOH BESAR ALIRAN ASYARIYAH (Telaah Perbandingan Atas Pemikiran Al-Asyari, Al- Baqillani, Al-Juwaini, dan Al-Ghazali) - AB, Hadariansyah (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2009)
The problem of human actions has been an important discoursein Islamic theology. The main problem here is that how humans actionsare understood in relation to God. Are human actions created by humanbeings themselves or by God? Muslim theologians have different answersto this question. This article discusses the opinions of the Asyâaritetheologians, namely al-Asyâari, al-Baqillani, al-Juwaini and al-Ghazali.Although these theologians are in the same school of Asyâarism, theyhave similar as well as different opinions on this important issue.